1989
DOI: 10.1210/jcem-68-2-317
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Hypothalamic-Pituitary-Gonadal Axis in Human Immunodeficiency Virus-Infected Homosexual Men*

Abstract: Serum total testosterone, total 17 beta-estradiol, LH, FSH, and PRL concentrations were measured by RIA in 59 homosexual men infected with the human immunodeficiency virus (32 clinically healthy antibody-positive men (HH+), 20 men with acquired immune deficiency syndrome (AIDS), and 7 men with AIDS-related complex (ARC). The results were compared with those of 26 antibody-negative homosexual men (HH-) who served as controls. The mean serum total testosterone concentration was significantly lower in the men wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(52 citation statements)
references
References 25 publications
2
48
0
2
Order By: Relevance
“…The level of prolactin in HIV-infected lactating women has not previously been measured. The role of prolactin in lactational amenorrhea in the absence of HIV-infection is well established and, from our results, appears to be intact among HIV-infected, lactating or recently weaned women, despite the presence of hyperprolactinemia found among HIV-infected men and women [32,33]. However, the significance of increased prolactin in these circumstances remains controversial [36].…”
Section: Prolactinmentioning
confidence: 74%
See 1 more Smart Citation
“…The level of prolactin in HIV-infected lactating women has not previously been measured. The role of prolactin in lactational amenorrhea in the absence of HIV-infection is well established and, from our results, appears to be intact among HIV-infected, lactating or recently weaned women, despite the presence of hyperprolactinemia found among HIV-infected men and women [32,33]. However, the significance of increased prolactin in these circumstances remains controversial [36].…”
Section: Prolactinmentioning
confidence: 74%
“…It has been shown to increase significantly in response to the stimulus of breastfeeding [26][27][28][29], diminish with the onset of non-exclusive breastfeeding [30] and fall precipitously after suckling has ended [31]. Hyperprolactinemia is also known to occur in up to one-fifth of HIVinfected non-lactating individuals [32,33] but has not been assessed in lactating HIV-infected women.…”
Section: Prolactinmentioning
confidence: 99%
“…However, other studies found no significant abnormality in the hypothalamic-pituitary axis (253,286). The low serum testosterone levels in men with AIDS are in some cases associated with high serum LH and FSH levels, implying that there is primary testicular failure (79). A possible reason for the testosterone secretory defect in these men is suggested by reports that cytokines released by the activated phagocytic cells of the immune system inhibit the steroidogenic response to human chorionic gonadotropin in vitro and presumably also the response to LH in vivo (57).…”
Section: The Human Testismentioning
confidence: 99%
“…Therapy with testosterone will always need to be carefully considered as there will always remain the potential for abuse by men wanting a cure for chronic fatigue and lack of energy or seeking their lost youth. Barreca et al, 1983Griggs et al, 1985a,b, 1989 Normal testosterone Increased Warner et al, 1992 DHT resistance …”
Section: Resultsmentioning
confidence: 99%
“…low CD4 count and weight loss (Raffi et al, 1991). Others have shown similarly reduced testosterone levels in patients with AIDS, but elevated gonadotrophins, suggestive of a primary gonadal defect (Croxson et al, 1989), while evidence of testicular atrophy and impaired spermatogenesis has been found in postmortem studies without inflammation or infection. (Welch et al, 1984).…”
Section: Infectionsmentioning
confidence: 92%